Design, synthesis and antibacterial activity against pathogenic mycobacteria of conjugated hydroxamic acids, hydrazides and O-alkyl/O-acyl protected hydroxamic derivatives. (15th May 2022) - Mavrikaki, Vasiliki; Pagonis, Alexandros; Poncin, Isabelle; Mallick, Ivy; Canaan, Stéphane; Magrioti, Victoria; Cavalier, Jean-François
Graphical abstract: Abstract: With the aim to discover new antituberculous molecules, three novel series of 23 hydroxamic acids, 13 hydrazides, and 9O-alkyl/O-acyl protected hydroxamic acid derivatives have been synthesized, and fully characterized by spectral 1 H NMR, 13 C NMR, HRMS) analysis. These compounds were further biologically screened for their in vitro antibacterial activities against three pathogenic mycobacteria - M. abscessus S and R, M. marinum, and M. tuberculosis – as well as for their toxicity towards murine macrophages by the resazurin microtiter assay (REMA). Among the 45 derivatives, 17 compounds (3 hydroxamic acids, 9 hydrazides, and 5O-alkyl/O-acyl protected hydroxamic acids) were nontoxic against murine macrophages. When tested for their antibacterial activity, hydroxamic acid 9 h was found to be the most potent inhibitor against M. abscessus S and R only. Regarding hydrazide series, only 7h was active against M. abscessus R, M. marinum and M. tuberculosis; while the O-acyl protected hydroxamic acid derivatives 14d and 15d displayed promising antibacterial activity against both M. marinum and M. tuberculosis. Since such hydroxamic- and hydrazide-chelating groups have been reported to impair the activity of the peptide deformylase, in silico molecular docking studies in M. tuberculosis peptide deformylase enzyme active site were further performed with 7h in order to predict the possible interaction mode and binding energy of this molecule at the molecular level.